1994
DOI: 10.1159/000139190
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Action of Orally Active 5-Lipoxygenase Inhibitor TMK688

Abstract: A topical application of 12-0-tetradecanoylphorbol-13-acetate (TPA) to mouse ear surface induces nonallergic inflammation, i.e. ear edema. Oral administration of 3-30 mg/kg of l-{[5’-(3”-methoxy-4”-ethoxycarbonyloxyphenyl)-2’,4’-pentadienoyl]aminoethyl}-4-diphenylmethoxypiperidine (TMK 688), a potent 5-lipoxygenase inhibitor with antihistamine activity, inhibited TPA-induced ear edema in a dose-dependent manner. TMK688 inhibited not only 5-lipoxygenase activity but also epidermal cyclooxygenase activity. 1 – {… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Oedema was induced in the right ear of mice by topical application of 4 g/ear of TPA in acetone [8]. The left ear (control) received vehicle (acetone, 20 L).…”
Section: Tpa-induced Mouse Ear Oedemamentioning
confidence: 99%
“…Oedema was induced in the right ear of mice by topical application of 4 g/ear of TPA in acetone [8]. The left ear (control) received vehicle (acetone, 20 L).…”
Section: Tpa-induced Mouse Ear Oedemamentioning
confidence: 99%
“…Oedema was induced in the right ear of mice by topical application of 4 µg/ear of TPA in acetone [8]. The left ear (control) received vehicle (acetone, 20 µl).…”
Section: Tpa-induced Mouse Ear Oedemamentioning
confidence: 99%
“…This suggested that neither cyclooxygenase inhibition nor antihistaminic activity were essential to the antiinflammatory action of linetastine. The antiinflammatory effect of oral linetastine is probably due to 5-LO inhibition [54]. Jiang et al [23] found oral administration of linetastine inhibited both TPA-promoted and non-TPApromoted skin tumor formation in 7,12-dimethylbenz[a]anthracene-initiated CD-1 mice.…”
Section: Leflunomidementioning
confidence: 99%